Improvement Of Self Alignment Footing System For Motor-Pump Rotating Shaft - Alkhanbashi, Maged Abdullah Ahmed (2019)
This project described the development of motorized shaft alignment system to be used in motor-pump machineries. Shaft alignment is vital to ensure the equipment able to operate for longer duration. It was well known that poor alignment causes the bearing failures, coupling wear or failure, increase energy consumption, bearing housing damage and bent rotors or crankshafts. In the past, misalignment issues were solved manually by using shims, however, this method having problematic issue such as skill requirement and time consuming. Alternatively, the shimless footing system were introduced to overcome this problem. This project described the improvement of current shimless design by introducing motorized system. It was notified the root causes of the previous design problems due to manufacturing quality (t-slot and normal screw that used). A new motorize self-alignment system was developed along with fabricate a new footing system. A new feature will be added to overcome delay response time, backlash, not accurate positioning, and ease for maintenance. A linear bearing and backlash free screw are the major component to solve the backlash problem, reducing response time needed to settle down the misalignment correction, and become more precise. The new design of block was fabricated with size of 100 mm x 200 mm x 100 mm. The drawing of the prototype is done by using solidworks software. The block made of aluminum and machined by CNC milling machine. Vibration sensor was added to measure the response of misalignment. The PID controller will do correction by controlling shaft position by mean of step motor drive. Finally, the test on the fabricated system will be done by using test rig. As expected the project got improved in terms of response time with more accurate position. The lowest record score 7 seconds to correct the misalignment in shaft speed 100 RPM, while it took 86 second for correction in shaft speed 1000 RPM.